UWM/UP joint study program: experience, problems, and future perspectives:to be presented at the 2nd Transatlantic Degree Program (TDP) workshop 'Education for a globalized world: transatlantic alliances and joint programs in business education and economics between the US, Canada and Germany' Tampa, Florida, 20 - 22 April 2007 - Hans-Georg Petersen (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2007)
The paper describes the exchange program in between the University of Wisconsin/Milwaukee and the University of Potsdam in the field of economics. It discusses in detail the development of the program, including the problems and challenges. Additionally a brief description of the curriculum is presented. Then the future possibilities of the Transatlantic Degree Program (TDP) are discussed and the influences and problems of the Bologna process analysed.
urn:nbn:de:kobv:517-opus-16147
Keywords: A2; A23; H0; Z10; 330; Joint study programs; Bologna process; economics curriculum; IASP Program of the DAAD; Transatlantic Degree Program (TDP); tuition fees; Wirtschaftsstudium; Auslandsaufenthalt; Internationale wissenschaftliche Zusammenarbeit; Studienfinanzierung; USA; Deutschland